Manejo de abelhas do gênero Xylocopa (Apidae, Xylocopini) para incremento da frutificação do maracujá-amarelo (Passiflora edulis f. flavicarpa Degener) - Junqueira, Camila Nonato (2012)
Passion fruit productivity does not achieve optimal levels in areas with low density or lack of effective pollinators like Xylocopa bees. These bees present appropriate size and foraging behavior for passion fruit pollination and are easily managed in trap nests. The aim of the study was to evaluate management procedures of X. frontalis and X. grisescens and assess the management effectiveness of these species to increase production and quality of yellow passion fruit in commercial orchards. During March 2008 to January 2010, nest management experiments were carried out at Água Limpa Experimental Farm, Uberlândia MG. Two entomological stations were built to shelter the trap-nests and to check the dynamics of occupation of both Xylocopa species. Each entomological station was populated with 192 trap-nests made of bamboo canes. Furthermore 12 nests of X. grisescens and 17 nests of X. frontalis were introduced to these stations. Experiments involving management effectiveness of these species in increase production and quality of yellow passion fruit were held from November/2010 to June/2011 in six crops areas in Araguari-MG (three experimental areas and three control areas). We introduced four nests/ha of X. frontalis and X. grisescens in the experimental areas (n=36 nests). Pollinators visitation rate, pollination tests and further fruits physicochemical characterization were carried out in all study areas before and after nests introduction. These nests were placed in entomological station built near the crop areas, with 48 other trap-nests. In the experiments conducted at the Experimental Farm, about 50% of females remained in their nests after transference and there was a higher females permanence in nests with brood cells (above 80%). There was an increase of 248% in the number of nests compared to the number of introduced nests, due to nest foundation (n=58) and nest reuse (n=14). Nest foundations were performed by females that emerged in the entomological station (n=22 nests) and by females from the surrounding area, which were attracted by trap-nests (n=36 nests). Transfer procedures did not affect nests development, because there was no significant differences regarding longevity, number of brood cells and sex ratio between introduced and founded nests. In crops areas nest introduction was successful regarding females permanence and new nests foundation. Nest management of X. frontalis and X. grisescens resulted in a decrease in visitation rate of thieves in two crop areas and in a significant increase in visitation rate of pollinators, yield and quality of fruits formed through natural pollination in one of the passion fruit crop areas. This study demonstrates that nests introduction of X. frontalis and X. grisescens and nesting substrates supply are efficient management techniques, thereby ensuring sustained pollination services which include increase in quality and yield of passion fruit. Parameters used to determine the optimal number of nests introduced in crop areas to increase passion fruit yield and how the proportion of natural remnants and farm practices influence bee populations and fruit set require further investigation.